The Service of Excellent on Course Program at MarkPlus, Inc Jakarta - Rattu, Nathaya Syahid; Hatta, Holila (Journal of Entrepreneurship, Management and Industry (JEMI), 2021)
This study aims to determine the service of excellent at MarkPlus. In service companies like MarkPlus, it is very important to maintain the performance to customers, but often fail to understand the desires or things that are considered important by customers. Therefore it is necessary to conduct research related to customer perceptions to get a better view of their needs. By using the Importance Performance Analysis (IPA) method, researchers try to find out the level of importance and quality of performance felt by customers who take part in the Executive Education Program. The questionnaire was distributed to 50 respondents who took part in the MarkPlus Executive Education Program. the validity and reliability of the questionnaire. IPA analysis shows that there are attributes that fall into quadrant I or top priority, which means the attributes in this quadrant are considered important by customers but the performance provided is not appropriate, including services that are not on time, services provided are not in accordance with the prices offered and complaints that are felt to have not been done quickly and reliably. This should be noted by MarkPlus, because these attributes are the focus of MarkPlus to improve the quality of its services in the Executive Education Program. The conclusion of the study showed that the quality of services provided was included in the excellent category with a percentage of 93.13% and this showed a high level of satisfaction from the respondents.